REPLACEMENT OF MISSING HALLUX WITH GLOVE TYPE SILICONE PROSTHESIS- A CASE REPORT - Arslan, Keyser (AMBER PUBLICATION, 2021)
Loss of hallux produces significant esthetic and functional deficiencies. The concealment of an amputated part with the help of prosthesis can shield an amputee from social stigma. Prosthesis for such patient must be comfortable to wear lightweight, durable, cosmetically pleasing easy to put on and remove. The prosthetic rehabilitation of an amputated finger/toe is considered when microvascular reconstruction is not possible, unavailable, unsuccessful, or unaffordable. Replacement by prosthesis offers psychological support and social acceptance in such cases. This clinical report describes a method to fabricate glove retained silicone toe prosthesis in a patient with greater toe loss.
Keywords: Missing hallux; Silicone prosthesis; Mechanical retention; Research & Experimental Medicine